DEVELOPMENT OF THE AUTOMATIC CONTROL SYSTEM OF PUMPING STATION FOR URBAN WATER SUPPLY - Pistun, Evgeniy; Yakymchuk, Natalia (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The analysis of the automatic control of water intake area of the pumping station, which is based on a controller with fuzzy logic and systematization using seasonally and hourly water consumption by using wavelet transforms.